2014
DOI: 10.1039/c4py00458b
|View full text |Cite
|
Sign up to set email alerts
|

From particles to stabilizing blocks – polymerized ionic liquids in aqueous heterophase polymerization

Abstract: Dispersions of polymerized ionic liquids (PIL) are a new class of reactive stabilizers for aqueous heterophase polymerizations, which are either hydrophilic or hydrophobic with regard to their reaction partner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…We and others recently demonstrated the emulsion polymerization of ionic liquid monomers and new applications of poly(ionic liquids) as all‐in‐one reactant and stabilizer for the synthesis of polymer latexes and hydrophobic powders which may lead to stable liquid marbles . These works demonstrated that PILs could also be employed as stabilizers in aqueous heterophase polymerization because of their similarity to polysoaps which have been employed in colloidal chemistry since the 1950s …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others recently demonstrated the emulsion polymerization of ionic liquid monomers and new applications of poly(ionic liquids) as all‐in‐one reactant and stabilizer for the synthesis of polymer latexes and hydrophobic powders which may lead to stable liquid marbles . These works demonstrated that PILs could also be employed as stabilizers in aqueous heterophase polymerization because of their similarity to polysoaps which have been employed in colloidal chemistry since the 1950s …”
Section: Introductionmentioning
confidence: 99%
“…14,[35][36][37] These works demonstrated that PILs could also be employed as stabilizers in aqueous heterophase polymerization because of their similarity to polysoaps 38 which have been employed in colloidal chemistry since the 1950s. 39,40 Magnetic ionic liquids were discovered in 2004 by Hayashi and Hamaguchi showing that ionic liquids with imidazolium Additional Supporting Information may be found in the online version of this article. cations with the paramagnetic anion FeCl 4 show a strong magnetic field response.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions between the different polymer blocks are assumed to be the hydrogen bonding between the NIPAm units and the protons in the imidazolium rings [50], as well as hydrophobic interactions between the bulky side groups in the PIL blocks [51]. Concentration of the polymer solutions has only a small effect on thermal behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, we have shown that in order to get stable block copolymer latexes with poly(ethylene glycol) as reductant, its molecular weight must be higher than about 2000 g mol −1 . [ 4 ] The following experimental facts and ideas should be considered in context: (1) the hydrophilic reductant forms the terminal group of the growing (block)copoly mer chain, (2) at the polymerization temperature above the lower critical solution temperature of PNIPAM, the polymer chains undergo both inter-and intrachain aggregation, and (3) the recently introduced principle of relative hydrophilicity (PRH) [ 40 ] meaning that for a given combination of hydrophilic substances, the one which is less hydrophilic behaves in common action hydrophobic. This principle indicates for the considered block copolymer formation reaction that as long as the intraparticle mobility is high enough, the morphology can change accordingly.…”
Section: Formation Mechanism Of Msp Morphologymentioning
confidence: 99%
“…This principle indicates for the considered block copolymer formation reaction that as long as the intraparticle mobility is high enough, the morphology can change accordingly. [ 40 ] The PRH is an important piece to consistently explain the experimental observations and to understand the formation of MSP morphology.…”
Section: Formation Mechanism Of Msp Morphologymentioning
confidence: 99%